The economic structure of trusts - Lau, M. W. (Oxford : Oxford University Press, 2011)
Providing an economic account of why trusts exist and how trust law should be shaped, this book explains the economic benefits of trusts as an extension of the law of property, arguing against accounts of trusts law grounded in the law of personal obligations. The theoretical model is then used to criticise recent developments in the law.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Trusts and trustees